Effect of freezing and thawing cycle properties of cement-stabilized macadam materials with self-prepared early-strength agents. (January 2019) - Lin, M; Guo, Y C; Tian, B S; Song, Y L
Abstract: Three types of cement-stabilized macadam materials and raw materials mixed with a self-made early-strength agent were prepared and subjected to freeze-thaw cycle tests. Based on the unconfined compression and freeze-thaw cyclic tests, the compressive strength and mass loss rate, and frost resistance coefficients of these samples were assessed and compared. The change of material properties caused by different content of early-strength agent was analyzed. The results show that three kinds of early-strength agents can improve the compressive strength and freezing resistance of cement-stabilized macadam. The compressive strength of cement-stabilized macadam with 2.0% anhydrous sodium sulfate and 1.0% triethanolamine is the best; the compressive strength is increased by 73.8%. Cement-stabilized macadam material with 1.5% anhydrous sodium sulfate and 1.0% triethanolamine has the best frost resistance, and its mass loss rate is reduced by 0.733%. The curves of mass loss rate and freeze-thaw cycle times of four groups of material are established, and the trend of positive correlation between the content of anhydrous sodium sulfate and the freezing resistance is obtained.